The Critique of Visual Violence and “Applied Aristotelianism” in M. Haneke’s “Funny Games” - Milerius, Nerijus (Problemos, 2015)
The article analyses the question of cinematic visual violence and the case of M. Haneke’s “Funny Games”. Serial products of contemporary visual culture are constructed in accordance with the rules of the so-called “applied Aristotelianism”. How the industry of visual entertainment redevelops Aristotle’s “Poetics” is especially evident in the films of entertaining visual violence. Aristotle’s theory is treated not only as the principle that provides legitimate basis to depiction of violence, but also as a rule that allows to achieve “an institutionalized catharsis”. The strong links between cinematic visual violence and “applied Aristotelianism” allow us to understand why the criticism of entertaining visual culture quite often coincides with the desire to deconstruct the laws of classical narration. It is precisely the strategy undertaken by Haneke in “Funny Games”. Haneke negates the two basic principles of Aristotelian poetics. Firstly, he deconstructs the experience of visual pleasure and, therefore, prevents the viewer from experiencing catharsis as reward. Secondly, by twice rewinding the same violent act, Haneke refocuses attention from the narration to the viewer, and turns the latter into the main “character” of the film. Both modifications transform “Funny Games” into the field of polemics with the industry of entertaining visual violence.